The Goan Identity far from Goa. The mechanisms of (re)construction of identity and the strategies of transmission of memory implemented by the Goan Catholic Community of Lisbon - Panizzi, Chiara (Transnational 20th Century. Literatures, arts and cultures, 2021)
The tiny State of Goa, now part of the Indian Union, has been for almost five centuries under Portuguese control and, inevitably this long lasting domination left tangible marks in Goan culture and identity, such that was created the expression hybrid indo-lusitan heritage. Starting from the analysis of the data collected through an ethnographic research, the aim of this article is to investigate the mechanisms of (re)construction of identity and the strategies of preservation and transmission of memory implemented by the Goan Catholic Community of Lisbon. Through the presentation of the life narratives of the interlocutors the processes of belonging and (re)construction of identity will be examine considering the transnational paths that concern not just the individuals but also their memories and identities.